Crystallographic and Thermal Studies of the Polymorphs of Tetraoxa[4]arene with Meta-Phenylene Linkers - Yuki Ishida; Tadashi Kawasaki; Akiko Hori (Crystals)
The three isomers of the tetraoxa[4]arene derivative, C24H16O4, which consist of two m-phenylenes and two phenylenes (meta 1, para 2, ortho 3), represent not only intriguing fundamental structures that induce molecular recognition toward non-porous adaptive crystals, but also attractive candidates for crystallographic polymorphism. In this study, we crystallized isomers 2 and 3, in comparison to isomer 1, in order to understand their stable orientations and the corresponding intermolecular interactions in the crystalline state. For example, m-phenylene derivative 1 exhibits polymorphism with both prismatic and block-shaped crystals. Therefore, we prepared p-phenylene derivative 2 and o-phenylene derivative 3, and their structures were fully characterized by SC-XRD, revealing two polymorphs of derivative 2, namely prismatic crystal 2-I and block-shaped crystal 2-II, along with changes to the crystal lattice parameters (2-Ia, 2-Ib, and 2-Ic) based on temperature dependence. In all of its crystal forms, derivative 2 adopts an O-shaped planar structure, where the p-phenylene units face each other. This suggests that the packing mode during the early stages of crystallization, rather than due to any remarkable changes in the molecular structure, directly affects the bulk crystal morphology. On the other hand, derivative 3 adopts a U-shaped vent structure and, to the best of our knowledge, does not form polymorphs. The Platon and Hirshfeld surface analyses indicated that the contributions to the crystal packing were C···C (av. 37.3% for 2-Ia, av. 38.2% for 2-II, and 18.7% for 3), C···H/H···C (av. 37.3% for 2-Ia, av. 38.2% for 2-II, and 18.7% for 3), and O···H/H···O (av. 17.8% for 2-Ia, av. 19.6% for 2-II, and 19.4% for 3), highlighting significant intermolecular CH···π interactions and pseudo-hydrogen bonding forms for derivative 2 and π···π interactions for derivative 3.